Cost-Effectiveness of a Therapeutic Tai Ji Quan Fall Prevention Intervention for Older Adults at High Risk of Falling. (10th January 2019) - Li, Fuzhong; Harmer, Peter; Eckstrom, Elizabeth; Fitzgerald, Kathleen; Akers, Laura; Chou, Li-Shan; Pidgeon, Dawna; Voit, Jan; Winters-Stone, Kerri
Abstract: Background: Data on the cost-effectiveness of proven fall prevention exercise interventions are limited. We aimed to establish the cost-effectiveness of Tai Ji Quan: Moving for Better Balance (TJQMBB) compared with a conventional exercise intervention for older adults at high risk of falling. Methods: We conducted a trial-based cost-effectiveness analysis involving 670 older adults who had a history of falling or impaired mobility. Participants received one of three interventions—TJQMBB, multimodal exercise, or stretching exercise (control)—each of which was implemented twice weekly for 24 weeks. The primary cost-effectiveness measure was the incremental cost per additional fall prevented, comparing TJQMBB and multimodal exercise to Stretching and TJQMBB to multimodal exercise, with a secondary measure of incremental cost per additional quality-adjusted life-year (QALY) gained. The intervention was conducted between February 2015 and January 2018, and cost-effectiveness was estimated from a health care system perspective over a 6-month time horizon. Results: The total cost to deliver the TJQMBB intervention was $202, 949 (an average of $906 per participant); for multimodal exercise, it was $223, 849 ($1, 004 per participant); and for Stretching, it was $210, 468 ($903 per participant). Incremental cost-effectiveness ratios showed that the multimodal exercise was cost-effective ($850 per additional fall prevented; $27, 614 per additional QALY gained) relative to Stretching; however, TJQMBB was the most economically dominant strategy (ie, having lower cost and being clinically more efficacious) compared with multimodal and stretching exercises with regard to cost per additional fall prevented and per additional QALY gained. TJQMBB had a 100% probability of being cost-effective, relative to Stretching, at a threshold of $500 per each additional fall prevented and $10, 000 per additional QALY gained. Sensitivity analyses showed the robustness of the results when extreme cases, medical costs only, and missing data were considered. Conclusions: Among community-dwelling older adults at high risk for falls, TJQMBB is a cost-effective means of reducing falls compared with conventional exercise approaches. Trial Registration: Clinicaltrials.gov (NCT02287740).